Efficient Delivery of Antimicrobial Peptides in an Innovative, Slow-Release Pharmacological Formulation - Naroa Serna; Hèctor López-Laguna; Patricia Aceituno; Mauricio Rojas-Peña; Eloi Parladé; Eric Voltà-Durán; Carlos Martínez-Torró; Julieta M. Sánchez; Angela Di Somma; Jose Vicente Carratalá; Andrea L. Livieri; Neus Ferrer-Miralles; et al. (MDPI AG, 2023)
Both nanostructure and multivalency enhance the biological activities of antimicrobial peptides (AMPs), whose mechanism of action is cooperative. In addition, the efficacy of a particular AMP should benefit from a steady concentration at the local place of action and, therefore, from a slow release after a dynamic repository. In the context of emerging multi-resistant bacterial infections and the urgent need for novel and effective antimicrobial drugs, we tested these concepts through the engineering of four AMPs into supramolecular complexes as pharmacological entities. For that purpose, GWH1, T22, Pt5, and PaD, produced as GFP or human nidogen-based His-tagged fusion proteins, were engineered as self-assembling oligomeric nanoparticles ranging from 10 to 70 nm and further packaged into nanoparticle-leaking submicron granules. Since these materials slowly release functional nanoparticles during their time-sustained unpacking, they are suitable for use as drug depots in vivo. In this context, a particular AMP version (GWH1-NIDO-H6) was selected for in vivo validation in a zebrafish model of a complex bacterial infection. The GWH1-NIDO-H6-secreting protein granules are protective in zebrafish against infection by the multi-resistant bacterium Stenotrophomonas maltophilia, proving the potential of innovative formulations based on nanostructured and slowly released recombinant AMPs in the fight against bacterial infections.